Potensi dan Tantangan Pelabuhan Makassar New Port terhadap Peningkatan Perdagangan di Kota Makassar - Kevin William Talebong; Seniwati Seniwati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Makassar New Port Port is an alternative port that is used only to accommodate containers that can no longer be accommodated by the Soekarno-Hatta port which has almost reached the maximum limit of container loads that can be accommodated. Even though this port has had a positive impact on the sustainability of the economy in Indonesia and Makassar, there are still several problems faced by this port. Such as the rejection made by fishermen who do not agree with the presence or construction of the Makassar New Port in Makassar because it interferes with their fishing activities. The port responded to this problem well by transmitting directly to the fishermen how to solve it. In this research, the author uses maritime diplomacy theory and international political economy theory in its creation. This research is also to obtain information about the potential and challenges of the Makassar New Port port.